Investigating the host finding behaviour of the weevil Phytobius vestitus for the biological control of the invasive aquatic weed Myriophyllum aquaticum - A. Pessina; L. Humair; R. Naderi; G. Röder; M.L. Seehausen; S. Rasmann; P. Weyl (Biological Control)
Biological control programmes involve pre-release studies that include host range tests to predict likely negative effects on native species. Behavioural responses of potential biological control agents to olfactory signals emitted by target and non-target species provide information on the host-finding and selection behaviour for safer agent selection. The weevil Phytobius vestitus (Coleoptera: Curculionidae) was identified as a potential biological control agent for the sustainable management of the aquatic weed Myriophyllum aquaticum (Haloragaceae). Using olfactometer-based bioassays, we analysed the host-finding and host-selection behaviour of P. vestitus across a variety of plant species closely related to M. aquaticum using a glass olfactometer. We further analysed the volatile organic compounds emitted by the target and non-target plant species to explain the weevil's observed preferences. We demonstrated that P. vestitus was able to recognise and discriminate between eight closely related Haloragaceae plant species and was significantly more attracted to the olfactory cues emitted by the target plant, M. aquaticum, compared to the other plant species. This study provides a first important indication of the specificity of P. vestitus and shows the role of plant chemistry in host selection and the possibility of refining host range assessment for potential biological control agents. However, exhaustive risk assessment for possible release into targeted new environments still requires further investigations.